New insight of some extracellular matrix molecules in beef muscles. Relationships with sensory qualities. (16th November 2015) - Dubost, A.; Micol, D.; Lethias, C.; Listrat, A.
Abstract : The aim of this study was to highlight the relationships between decorin, tenascin-X and type XIV collagen, three minor molecules of extracellular matrix (ECM), with some structural parameters of connective tissue and its content in total collagen, its cross-links (CLs) and its proteoglycans (PGs). In addition, we have evaluated impact of these minor molecules on beef quality traits. The relative abundance of these molecules was evaluated by western blot analysis in Longissimus thoracis (LT) and Biceps femoris (BF) muscles from Aberdeen Angus and Blond d'Aquitaine beef breeds. Decorin and tenascin-X were more abundant in BF than in LT (1.8 v . 0.5 arbitrary units (AU), respectively, P <0.001, and 1.0 v . 0.6 AU, P <0.05). There was no muscle effect for collagen XIV content. Decorin and tenascin-X relative abundance were positively correlated with perimysium and endomysium areas and with collagen characteristics (total, insoluble and CLs). Decorin was negatively correlated with total PG content and positively with tenascin-X. Collagen XIV was correlated with any of parameters measured. To assess the impact of decorin, tenascin-X and collagen XIV and of their ratios to total collagen and PGs on shear force and quality traits we realized, respectively, a multiple-linear regression analysis and a Pearson's correlation analysis. Decorin and tenascin-X relative abundance were, respectively, negatively and positively involved in juiciness. Decorin relative abundance was also negatively involved in abnormal flavour and positively in overall liking. The ratio of decorin to total collagen and PGs was negatively correlated to juiciness, together with collagen XIV ratio to total PGs. The ratios of decorin, tenascin-X and collagen XIV to total PGs were positively correlated to sensory tenderness, negatively to abnormal beef flavour and positively to overall liking. The ratio of decorin to total collagen was also negatively correlated to abnormal flavour and positively to overall liking while its ratio to total PGs was positively correlated to beef flavour and overall liking. Results of the present study highlighted for the first time the possible role of minor ECM molecules on beef quality traits. In addition, variations of meat texture and more generally of sensory qualities would depend not only to the quantity of total collagen and of its CLs, but also of components of ECM such as decorin, tenascin-X and collagen XIV and of their ratios to total collagen and PGs.